Educational Bureaucracy in Indonesia and Its Implications for School Governance - Syifaurrahmah, Sabrina; Milda, Jefpi; Sirozi, Muhammad (FKIP - Universitas Riau, 2025)
The education bureaucracy in Indonesia has an important role in maintaining national education standards through regulating and supervising the implementation of education policies. However, in practice, the education bureaucracy is often perceive as slow, overly formal and bureaucratic. Long administrative procedures can hamper schools' flexibility in management, such as decision making, financial and budgetary management, teacher recruitment and management, and curriculum and learning systems development. This article aims to analyzed the implications of the education bureaucracy on school governance in Indonesia using a library research approach and descriptive analysis. The results showed that a rigid and centralized education bureaucracy can inhibit creativity and innovation at the school level, but on the other hand, it is also needed to ensure the effectiveness of policy implementation and equitable distribution of education services. Therefore, a more adaptive and efficient education bureaucracy reform is needed, such as decentralized authority, simplified regulations, increased transparency and accountability, and developed the capacity of education human resources, so that schools can have more space to innovate in improved the quality of education.